PENERAPAN E-GOVERNMENT UNTUK PENINGKATAN PELAYANAN PUBLIK DAN POTENSI DESA DI KAMPUNG KWEEL KABUPATEN MERAUKE - Prasetya, Muhammad Novan; Agus Nisfur; Aenal Fuad Adam (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The implementation of e-government-based public services is an effort by the government to enhance the quality of services and governance, making them more effective and efficient. This, in turn, enables the maximization of services to the community. Kampung Kweel serves as a buffer village in the conservation area and is also the center of the Yeinan Tribe, one of the oldest tribes in South Papua. Additionally, Kampung Kweel is a model self-reliant village that collaborates with Musamus University Merauke. To reach Kampung Kweel, one must pass through the Wasur National Park. Despite the various potentials in the area, the village governance system currently relies on manual methods, leading to suboptimal service delivery to the community and inadequate dissemination of information about the village's potential. This community service project is a continuation of previous research aimed at establishing Kampung Kweel as a model self-reliant village, focusing on three areas: Natural Resources and Management, Human Resources and Village Management, and the Existence of Local Wisdom. The goal of this community service is to assist the village government in addressing existing issues by implementing e-government in the governance system of Kampung Kweel, Merauke Regency. The project will be conducted in several stages. First, analyzing the issues in the implementation of e-government in Kampung Kweel. Next, create Data Flow Diagrams (DFD), Data Flow Diagrams (DFD), and Flowcharts. The final stage involves designing a website and a MySQL database. The implementation of e-government in Kampung Kweel is expected to help the village government provide responsive public services, facilitating the community in obtaining information and disseminating the potential of Kampung Kweel for investors and tourists interested in investing in the village. The outcomes of this community service will be published in the Community Service Journal (JPKM), a nationally accredited SINTA 3 journal, along with videos of the service activities and publications in both print and online media